A new species of the genus Tripylina Brzeski, 1963 (Nematoda: Enoplida: Trischistomatidae) from Shanxi province, China - Xu, Yu Mei; Zhao, Zeng Qi; Wang, Jian Ming; Zheng, Jing Wu (Zootaxa, 2013)
Tripylina puxianensis n. sp. is described and illustrated from Shanxi province, China. It is characterized by having a triangular dorsal tooth, pointing towards the ventral side, anterior to two sub-ventral teeth, with dorsal and sub-ventral teeth similar in shape and size; one ventromedian seta in the cervical region; vulva with protruding lips, absence of post-uterine sac; and a pair of setae on the tail; male not found; female body length 1048–1331 μm, a = 25.5–33.8, b = 5.5–6.2, c = 14.4–23.1, c’ = 2.1–3.5 and V = 56.1–68.5%. The phylogenetic relationships among species in the genus Tripylina were analyzed using data from the SSU (small subunit) and D2/D3 expansion segments of the LSU (large subunit) rDNA. These analyses confirmed that T. puxianensis n. sp. is different from other members of the genus for which sequences are available.